A Case of Money Laundering in the Education Sector – Analysis of Operational Methodology - Zahra, Syeda Naureen (Journal of Pakistan Administration, 2021)
For us in the taxation system, the first week of every quarter is always the busiest. Hordes of taxpayers storm the offices of Commissioners, Inland Revenue, for exemption certificates. These certificates are issued by the Commissioner after deposit of taxes in advance by the taxpayers for the whole year so that they wouldn’t have to pay withholding tax on any further transactions. It was on one such Monday morning of the first week of January when Maheen Hussain, Commissioner Inland Revenue (CIR), Corporate Regional Office Lahore, was exposed to the notorious world of money laundering.
Keywords: Money Laundering; Education Sector; Analysis; Operational Methodology